Digitalizace raně novověkých pramenů : případ normativních nařízení pro Moravu v raném novověku - Zbyněk Sviták (Studia Historica Brunensia, 2017)
The paper presents a new project, focused on the digitization of the normative regulations from the Early Modern Period for Moravia. It is aimed at the description of their function in society and emphasizes their significant role for the sovereign's regulation of the behaviour of the populace in various areas of life. Despite that, they have not been systematically treated so far by researchers. Digitization is to help make this important source collection accessible.